The Mummy : Quest for the Lost Tribes - Jacobovici, Simcha; Zann, Lenore (USA 1999)
Purple with rage, The Mummy roars his way through 60 minutes of cartoon adventure, straight from the Kids' WB television show's archives. Young Alex O'Connell and his archeologically inclined parents race to undo a few excavation faux pas: resurrecting the mummy Imhotep, unearthing the Book of the Dead, permanently clamping the Manacle of Osiris onto Alex's wrist. Only the Lost Scrolls can help. An exhaustive search exposes this glam family to skeleton warriors, hungry scarabs, and huge shark-toothed sand worms. It's a Jonny Quest- meets-Indiana Jones extravaganza in which kids endure, supernatural evil creatures happen, and corny jokes abound. This "feature-length adventure" merely streamlines the series' first season, bridging together episodes 1, 12, and 13 with snippets and helpful narration from deleted shows. Cool effects, stimulating animation, and an engaging story that propels the O'Connells around the globe (in their personal dirigible, no less) should thrill 8- to 13-year- olds. The DVD version includes episode 6 as a bonus.
After accidentally raising an evil mummy from the dead eleven-year-old alex oconnell is every kids hero as he narrowly escapes one perilous event after another. He and his family must race across the globe to find the lost scrolls that will unlock the powers of the magical manacle & defeat the enemy Studio: Uni Dist Corp. (mca) Release Date: 01/06/2004 Starring: Animated Run time: 66 minutes Rating: Nr Director: Eddy Houchins
Language : English Subtitle : English
Keywords: Animation